Deer Population Growth in the Bangabandhu Safari Park in Bangladesh - Hossen, Amir; Ahsan, M Farid; Kamruzzaman, Mohammad (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Abstract Not Available Asiat. Soc. Bangladesh, Sci. 43(1): 125-127, June 2017